ANTI-INFLAMMATORY ACTIVITY OF FICUS DALHOUSIAE MIQ ROOTS ETHANOLIC EXTRACT IN WISTAR ALBINO RATS - Ghori, Syed Safiullah; Khan, Mohib; Tabassum, Rana (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of the present investigation was to evaluate the anti-inflammatory activity of Ficus dalhousiae Miq roots ethanolic extract (FDREE) in Wistar albino rats using carrageenan and formalin induced paw edema model. Methods: Plant material was collected from Tirupati, A.P, during the month of June 2014.The roots were made free from dust and foreign material and dried under shade at room temperature. After a week, the roots were powdered and passed through a sieve. The powder was weighed (500 g) and was extracted by successive solvent extraction process. The total yield of the ethanolic extract was 17.6%. Phytochemical screening was carried out for the detection of the phytoconstituents by simple qualitative methods. The dosing was designed as per the acute toxicity study reported earlier.The anti-inflammatory activity was performed by carrageenan and formalin induced paw edema model at three different doses, 150 mg/kg, 300 mg/ kg and 600 mg/kg. Wistar rats weighing (130-150 g) of either sex were used for the study. Results: There was a significant reduction of elevated paw volume in the test groups observed in both carrageenan and formalin induced paw edema models. The percentage inhibition of inflammation was also high in the test groups compared with the negative control. Conclusion: FDREE exhibited anti-inflammatory activity in both acute and subacute experimental models which provides the evidence of its use as a potent anti-inflammatory drug. Keywords: Ficus dalhousiae roots ethanolic extract, Carrageenan, Formalin, Intraperitonial.